Innate immunity in the postmortem brain of depressed and suicide subjects: Role of Toll-like receptors - Pandey, Ghanshyam N.; Rizavi, Hooriyah S.; Bhaumik, Runa; Ren, Xinguo (Brain, behavior, and immunity, 2019)
•The expression of several TLRs is increased in prefrontal cortex of depressed suicide subjects.•There is a dissociation in gene and protein expression of several TLRs in depressed suicide subjects.•These findings suggest an abnormality of innate immunity in depression and suicide. Abnormalities of Toll-like receptors (TLRs) have been implicated in the pathophysiology of depression and suicide. Interactions of TLRs with pathogen-associated molecular patterns (PAMP) and damage-associated molecular patterns (DAMP) initiate signaling through myeloid differentiation primary response-88 (MyD88) and produce cytokines through the activation of the transcription factor nuclear factor kappa beta (NF-kB). We have earlier shown an increase in the protein and mRNA expression of TLR3 and TLR4 in the prefrontal cortex (PFC) of depressed suicide (DS) subjects compared with normal control (NC) subjects. To examine if other TLRs are altered in postmortem brain, we have now determined the protein and mRNA expression of other TLRs (TLR1, TLR2, TLR5, TLR6, TLR7, TLR8, TLR9 and TLR10) in the PFC of DS, depressed non-suicide (DNS), non-depressed suicide (NDS) and NC subjects. We determined the protein expression by Western blot and mRNA expression levels by real-time PCR (qPCR) in the PFC of 24 NC, 24 DS, 12 DNS and 11 NDS subjects. Combined with our previous study of TLR3 and TLR4, we found that the protein expression of TLR2, TLR3, TLR4, TLR6 and TLR10, and mRNA expression of TLR2 and TLR3 was significantly increased in the DS group compared with NC group. This study demonstrated that certain specific TLRs are altered in DS subjects, and hence those TLRs may be appropriate targets for the development of therapeutic agents for the treatment of suicidal behavior.